Assessment of Coating Performance on Waterwalls and Superheaters in a Pulverised Fuel-Fired Power Station - Simms, Nigel J.; Seraffon, Maud; Pidcock, Andrew; Davis, Colin (Springer, 2017)
Protective coatings offer one route to increase the lives of heat exchangers in pulverised fuel power plants. A range of candidate coatings have been exposed on the waterwall and superheaters of a 500 MWe UK power station unit for periods of up to ~4 years (24,880 operating hours), during which time this unit was fired on a mixture of UK and world-traded coals. Both nickel- and iron-based candidate coatings were included, applied using high velocity oxy-fuel or arc-wire process; a selection of these also had a surface sealant applied to investigate its effectiveness. Dimensional metrology was used to evaluate coating performances, with SEM/EDX examinations used to investigate the various degradation mechanisms found. Both the waterwall and superheater environments generated their characteristic corrosion damage morphologies which depended on the radial positions around the tube. Coating performances were found to depend on the initial coating quality rather than composition, and were not improved by the use of a sealant.
Keywords: Coatings; Fireside corrosion; Pulverised fuel combustion; Waterwalls and superheaters